2014
DOI: 10.1177/0148607114526450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, Clinical Consequences, and Treatment of Enteral Feed Intolerance During Critical Illness

Abstract: Intolerance occurs frequently during EN in critically ill patients and is associated with poorer nutrition and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
6
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(261 citation statements)
references
References 21 publications
(34 reference statements)
11
225
6
8
Order By: Relevance
“…Despite the problems with definition, current evidence supports the concept that FI occurs frequently and is associated with adverse outcomes in critically ill patients. In an international observational cohort study of 1888 ICU patients, the frequency of FI (defined as GRV ≥200 ml) was 30.5% and was associated with worse nutrition adequacy (56% vs. 64%, P  < 0.0001), increased ICU stay (14.4 vs. 11.3 days, P  < 0.0001), and increased mortality (30.8% vs. 26.2%, P  = 0.04) [8]. In a retrospective observational study, Reintam et al observed that the frequency of FI and the association between FI and mortality varied widely and depended on the definition used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the problems with definition, current evidence supports the concept that FI occurs frequently and is associated with adverse outcomes in critically ill patients. In an international observational cohort study of 1888 ICU patients, the frequency of FI (defined as GRV ≥200 ml) was 30.5% and was associated with worse nutrition adequacy (56% vs. 64%, P  < 0.0001), increased ICU stay (14.4 vs. 11.3 days, P  < 0.0001), and increased mortality (30.8% vs. 26.2%, P  = 0.04) [8]. In a retrospective observational study, Reintam et al observed that the frequency of FI and the association between FI and mortality varied widely and depended on the definition used.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the problems with definition, FI has been suggested to occur frequently and to be associated with adverse outcomes in critically ill patients [1, 6]. Nevertheless, the exact role of FI with regard to mortality remains controversial [811]. It is uncertain whether FI simply represents an epiphenomenon of illness severity or harm from inadequate enteral nutrition (EN) and/or the use of parenteral nutrition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Effective enteral nutrition, however, requires functioning gastrointestinal tract, often missing in the critically ill patient [24]. The factors neces-sary for the maintenance of the physiological structure and mucosal perfusion (Figure 1), are often compromised due to circulatory disturbances in patients in an ICU.…”
Section: The Correlation Between Gastric Mucosal Perfusion and Emptyimentioning
confidence: 99%
“…However, the defi nition of intolerance is variable. The incidence of interrupted EN therapy due to intolerance was 30.5 % in a cohort of 1888 ICU patients in the 2009 International Nutrition Study [ 38 ]. The most commonly reported intolerances were large gastric residual volumes (61.6 %) and vomiting or diarrhea (36.6 %).…”
Section: Delays and Obstacles To Feeding In Critical Carementioning
confidence: 99%